O ensino por meio da literatura de cordel - Santos, Alzanira de Souza (2016)
This work is the result of a research carried out in the Professional Masters in Technological Teaching – MPET, at the Federal Institute of Education, Science and Technology of Amazonas – IFAM/CMC. Its theme is teaching through Cordel Literature and presents the following problem: how is it possible to narrate the experiences of a teacher who uses Cordel Literature in teaching as a way of encouraging other teachers to use it for the same purpose? Due to the problem, the objective is to narrate the experiences of a teacher who uses Cordel Literature in teaching as a way of encouraging other teachers to use it for the same purpose. In order to reach this goal, we chose the autobiographical method and the qualitative research. In the first chapter, the experiences, the life trajectory of the researcher and the teaching work are narrated, in a course intersected with the Cordel Literature. In the second chapter, an episode is described, in which the researcher, as a student, in continuing education, uses the Cordel Literature as a contribution to teaching. In the third chapter, as an end product of this research, an online portfolio (www.caldogrosso.wordpress.com) is presented as a contribution to teaching through Cordel Literature. It is expected that research of this nature, which approaches the trajectory and experiences of teachers, the use of Cordel Literature in teaching and dissemination in the portfolio, be stimulated, become known and bring data important for the debate regarding the issues of educational research.